Legal Autonomy vs. Political Power: What is the Role of the European Court of Justice in the European Integration? - Rufat R. Babayev (Romanian Journal of European Affairs, 2007)
The European Court of Justice, founded as one of the main institutions of the European Union, has greatly contributed to further deepen the integration process. At the same time, the ECJ is one of the most controversial institutions. The article strives to present the role of the Court of Justice within the European architecture, analysing the debate between the two most important theoretical frameworks in the field: the legal autonomy approach and the political power approach.